Spatial Approach on Detection of Land Use Land Cover Changes of Puttur taluk, Karnataka - Sowmya NJ, Prasad Pujar, Sandeep J Nayak, Madhu S R (International Journal of Advanced Science and Technology, 2020)
Increasing population changes the land cover which affects the environment or socio-economic changes. This study deals with the quantification of impacts of natural changes and human activities on the land covers over time in Puttur taluk of Karnataka state. Satellite imageries for the years 2008, 2013 and 2019 are obtained from NRSC, Hyderabad. The study area is classified as water bodies, mixed forest, agricultural land, built-up land, barren land and river bed. To process satellite imageries and assess quantitative data for land-use change ArcGIS and ERDAS software areused. The study reveals that significant land use transformation converting mixed forest (23%) into built-up land (126%) and agricultural land (24%) exhibiting loss of productive lands may haveresulted due to change in living style and increased population. Hence, proper management is required to balance the socio-economic development of the area.